The politics of the New Germany - Green, Simon 1971- (Routledge, 2012)
the Politics of the New Germany continues to provide the most comprehensive, authoritative and up-to-date textbook on contemporary German Politics. The text takes a new approach to understanding politics in the post-unification Federal Republic. Assuming only elementary knowledge, it focuses on a series of the most important debates and issues in Germany today with the aim of helping students understand both the workings of the countrys key institutions and some of the most important policy challenges facing German politicians. Written in a straightforward style by three experts, each of the chapters draws on a rich variety of real-world examples. In doing so, it highlights both the challenges and opportunities facing policy-makers in such areas as foreign affairs, economic policy, immigration, identity politics and institutional reform. The book also takes a birds-eye view of the big debates that have defined German politics over time, regardless of which political parties happened to be in power. It pinpoints three key themes that have characterised German politics over the last sixty years; reconciliation, consensus and transformation. The book is a comprehensive, yet highly accessible, overview of politics in 21st Century Germany and should be essential reading for students of politics and international relations, as well as of European and German studies.